HUBUNGAN KARAKTERISTIK INDIVIDU DAN KOMPETENSI DENGAN KEPATUHAN PEMAKAIAN ALAT PELINDUNG DIRI PADA TENAGA RADIOLOGI DI RUMAH SAKIT BINA KASIH MEDAN - Hotben Lubis; Elisabeth Dame Manalu; Bahtera Bin David Purba (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2020)
Various efforts to prevent work accidents and protect workers with the use of personal protective equipment (PPE), but still often found workers who are not obedient in using PPE. To find out the relationship between individual characteristics and competencies based on the Compliance with the Use of Personal Protective Equipment on Radiology Workers This type of research is a quantitative study with a cross sectional approach that is to find the relationship between individual characteristics and competencies with the use of PPE. The population in this study were all radiologists who worked at the Bina Kasih Medan hospital. The sampling technique in this study was simple random sampling, sampling was done randomly using lottery so that each element in the population had the same opportunity to become a research sample. The results of this study indicate that there is a relationship between years of service (p = 0.001), training (p = 0,000) with compliance with the use of personal protective equipment (PPE) at Medan Bina Kasih Hospital in 2018. And there is no knowledge relationship (p = 0.051), age (p = 0.783), gender (p = 0.371), education (p = 0.141) with compliance with the use of personal protective equipment (PPE) at Bina Kasih Medan Hospital in 2018. It is expected that hospital management will hold Radiographer training regularly by both formal and non-formal educational institutions (professional organizations) through training in workshop training and the like. Keywords: Age, Gender, Work Period, Training, Knowledge, Education Level and Radiographer